Utilization of Waste Based Construction Materials Advancing Towards a Green Economy - Setiyono, Setiyono; Binti Abd Wahid, Nurul Bahiyah (Journal of Business Management and Economic Development, 2025)
The construction industry's growing environmental impact necessitates the adoption of sustainable materials and practices. This study explores the integration of waste-based materials plastic waste, glass waste, and fly ash into construction applications as an innovative approach to reducing environmental degradation and promoting a circular economy. Chemical recycling, photocatalytic conversion, and thermochemical processes enhance the potential of plastic waste in construction, particularly in road infrastructure. Similarly, waste glass powder (WGP) improves the mechanical properties of geopolymer concrete, while crushed glass serves as a sustainable substitute for natural sand in concrete production. Additionally, fly ash contributes to cement replacement, reducing carbon emissions and improving the long-term durability of concrete structures. The findings indicate that incorporating waste-based materials into construction reduces material costs by 15–30% and enhances durability by up to 40%, highlighting both economic and environmental benefits. Despite these advantages, challenges such as material variability, processing costs, and market acceptance remain key obstacles. Overcoming these barriers requires coordinated efforts among policymakers, industry stakeholders, and researchers to establish standards, incentives, and awareness programs that facilitate the transition towards sustainable construction practices.